Konsep Istihsan al-Shatiby dan Relevansinya ‎ dengan Pembaharuan Hukum Islam - darmawan darmawan (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The aim of this article is to discover the definition and concept of istihsan according to al-Shatiby. It also highlights the objective of al-Shatiby’s renewal of Islamic law with istihsan as one of his methods. According to him, istihsan is the abandonment of legal ruling arrived at by conventional evidence and the adoption of an alternative ruling derived from inferior evidence. On the other word, it is putting forward specific welfare at the expense of qiyas or conventional evidence because harms will certainly be inflicted whenever qiyas or conventional evidence is observed. Meanwhile, renewal of Islamic law simply means a movement to exercise ijtihad to produce legal rulings capable of answering the problem posed by the modern science and technology. It tries at its best to realize the objectives of Islamic law so that it answer the problems of ever-changing society. In so doing, there is relevance between the concept of istihsan and the renewal of Islamic law, especially in the aspect of maqasid al-shari‘ah.